Characterizing the evolution of the EU R&D intensity gap using data from top R&D performers - Federico Biagi; Juraj Stančík (European Regional Science Association (ERSA), 2012)
In this paper we look at the evolution of the R&D intensity gap between the EU and its major competitors using data from the Industrial Scoreboard covering the period 2002-2010. We focus on R&D intensity and we assess whether the gaps relative to major competitors arise from differences in industrial composition (structural component) or differences within sectors (intrinsic component). The paper is divided in two parts. In the first part of the paper we first present the evolution of the R&D intensity gap between the EU and its major competitors (US, Japan, BRIC, Asian Tigers) and then we look more closely at the role and evolution of the structural and intrinsic component for each pair-wise comparison, by looking at four basic macro-sectors defined in term of their R&D intensity. In the second part of our work we concentrate on the EU-US R&D intensity gap and, by applying firm level analysis, we test whether the results obtained by the statistical decomposition of aggregate R&D intensity are confirmed. In particular we test whether there is evidence of across-sector variability in R&D intensity and whether, within sectors, EU and US firms are performing differently, controlling for size, cyclical effects, common macroeconomic shocks and company's age. Age is important for at least two reasons. First, young companies might have more problems in finding access to funds necessary in order to invest in R&D. Second, young companies might have to be especially aggressive in terms of innovation if they want to enter and succeed in markets where incumbents already exist. Therefore, our aim here is also to document the age profile for R&D intensity and to verify whether the R&D intensity gap between EU and non-EU companies is related to age of the firm. Finally we check if R&D intensity is affected by the abundance of internal funds (as captured by the profit/sales ratio), if this relationship changes with the age of the company and if the latter shows across-regional variation. Our results from firm level analysis indicate that there is evidence of strong across-sector variation and some evidence of within-sectors-across-region variation, which –however- is not always in favour of the US. Moreover we find that R&D intensity tends to decrease as firm size increases (as measured by the number of employees), that the age profile for R&D intensity behaves very differently in the two regions and that young companies in the EU exhibit a much higher reactivity to lagged profits-to-sales ratio, when compared to their US counterpart. We believe that this is an indication that the conditions for accessibility and cost of funds differ significantly across the two regions.
Keywords: L16; O30; O57; 330; R&D Intensity; EU R&D gap